THE ORIGIN AND EVOLUTION OF SILICA-SATURATED ALKALIC SUITES: AN EXPERIMENTAL STUDY - Nekvasil H.; Dondolini A.; Horn J.; Filiberto J.; Long H.; Lindsley D.H. (My University, 2004)
Experimental simulation of incremental crystal fractionation of a hy-normative hawaiite indicates that the spectrum of compositions from mildly alkalic hawaiite to sodic rhyolite found in silica-saturated alkalic suites of the ocean islands and continental hotspots and rifts can be produced by fractionation at 9·3?kbar with bulk water contents >?0·5?wt?% (in the hawaiite) at fO2 ?1·5 log units below the fayalite–magnetite–quartz buffer (FMQ). Along this path, mildly alkalic basalt becomes increasingly alkalic because of the domination of clinopyroxene in the early fractionating assemblage and suppression of plagioclase. Kaersutite dominates at intermediate temperatures and results in stronger silica enrichment as the melt evolves to rhyolite. The fractionation assemblages are strongly pressure-sensitive. At mid-crustal pressures, melts become potassic rather than sodic. At shallow conditions, the abundance of early olivine produces strong silica enrichment and subalkalic total alkalis to silica ratios. Natural mineral assemblages from silica-saturated alkalic suites show a polybaric history with fractionation at ?30?km depth followed by decompression of liquids residual to this fractionation and crystallization, but not extensive fractionation, of lower-pressure assemblages. Equilibrium crystallization paths suggest that partial melting of hawaiite could produce the intermediate members of these suites provided that sufficient water was available in the source region.